Assessing critical thinking of postgraduate students - Saadati, Farzaneh; Ahmad Tarmizi, Rohani; Bayat, Sahar (Elsevier, 2010)
The purpose of this research is to check reliability of a non standard test for measuring two skills of critical thinking. We compared the result of this study with that was performed with WGCTA-SF as a common standard test for measuring the critical thinking skills.